1978
DOI: 10.1002/cpt1978236644
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide kinetics in renal failure

Abstract: Furosemide kinetics were studied in normal volunteers and patients with renal failure. Comparison of results from intravenous bolus and intravenous infusion in normal subjects showed no significant model dependency of estimations of furosemide clearance, although the average clearance by fitting to a one-compartment model was 16% higher than that obtained by fitting to a two-compartment model. Normal subjects had a total body clearance of furosemide of 1.53 +/- 0.11 (SE) ml/min/kg, a volume of the central comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 3 publications
2
24
1
Order By: Relevance
“…Regarding the pharmacology, intestinal reabsorption of 40 -90% has been reported in subjects with advanced CKD (65), yet altogether reabsorption seems diminished (154). Although a clear relationship between reabsorption and measures of GFR has not been documented in CKD, this could contribute to furosemide resistance.…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 99%
“…Regarding the pharmacology, intestinal reabsorption of 40 -90% has been reported in subjects with advanced CKD (65), yet altogether reabsorption seems diminished (154). Although a clear relationship between reabsorption and measures of GFR has not been documented in CKD, this could contribute to furosemide resistance.…”
Section: Does Kidney Disease Affect the Actions Of Furosemide?mentioning
confidence: 99%
“…Whilst a number of pathophysiological factors such as gastro-intestinal oedema, gut motility and local blood flow at the absorption site may be contributory factors to this reduction in bioavailability, the decrease is less than has been observed for frusemide. In studies with frusemide in patients with advanced renal failure, values of 0.43 (Tilstone & Fine, 1978) and 0.46 (Rane et al, 1978) were reported.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…It is highly bound to plasma proteins (6)(7)(8)(9)(10)(11)(12) and gains access to its site of action in the kidney lumen primarily through active secretion via the nonspecific organic acid secretory pathway (13)(14)(15). Previous studies have shown that renal disease can effect dramatic changes in the pharmacokinetics of furosemide (6,11,(16)(17)(18)(19)(20), including impaired plasma protein binding in uremics (7,11), nephrotics (10,11), and anephric patients (6). The degree of binding of furosemide to plasma proteins in kidney transplant patients has not been reported.…”
Section: Introductionmentioning
confidence: 99%